Évolution de la fécondité et des comportements féconds dans la vallée du Ntem (Sud-Cameroun) depuis 1940 - Hélène Pagezy; Daniel Bley; Olivier Bernard (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
A retrospective fertility survey has been conducted in 325 women from 13 villages of the Ntem valley (southern Cameroon) and 62 teenagers from Ma’an secondary school, over 15 years old. The important increase of fertility related to the disappearing of the primary sterility has been accompanied with women’s changing attitudes, aspirations and sexual behaviours in a context of mobility related to higher school levels. Theses phenomenons are likely to preceed and announce the future demographic transition as usually observed in most developing countries.